2015
DOI: 10.1111/tbed.12399
|View full text |Cite
|
Sign up to set email alerts
|

Newly Emerged PorcineDeltacoronavirusAssociated With Diarrhoea in Swine in China: Identification, Prevalence and Full-Length Genome Sequence Analysis

Abstract: To identify and characterize aetiologic agent(s) associated with an outbreak of a severe diarrhoea in piglets in Jiangxi, China, in March 2015, a nested reverse transcription-polymerase chain reaction (RT-PCR) for the detection of porcine deltacoronavirus (PDCoV) was developed. A survey based on the nested RT-PCR established indicated that the monoinfection of PDCoV (33.71%) and coinfection of PDCoV (19.66%) with porcine epidemic diarrhoea virus (PEDV) were common in diarrhoeal pigs in Jiangxi, China. A high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
230
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(245 citation statements)
references
References 20 publications
11
230
4
Order By: Relevance
“…Porcine deltacoronavirus was first identified in swine specimens collected in 2009 in Hong Kong (Woo et al., ). It was identified later in several states of USA (Li et al., ; Marthaler, Jiang, Collins, & Rossow, ; Wang, Byrum, & Zhang, ) and has now spread to South Korea, mainland China, Thailand and Laos (Lee & Lee, ; Lee et al., ; Lorsirigool et al., ; Madapong et al., ; Song et al., ). The emergence of PDCoV was most often associated with clinical infection symptoms including diarrhoea, vomiting and dehydration in pigs, especially in sucking and nursing piglets (Janetanakit et al., ; Ma et al., ; Marthaler, Raymond et al ; Song et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine deltacoronavirus was first identified in swine specimens collected in 2009 in Hong Kong (Woo et al., ). It was identified later in several states of USA (Li et al., ; Marthaler, Jiang, Collins, & Rossow, ; Wang, Byrum, & Zhang, ) and has now spread to South Korea, mainland China, Thailand and Laos (Lee & Lee, ; Lee et al., ; Lorsirigool et al., ; Madapong et al., ; Song et al., ). The emergence of PDCoV was most often associated with clinical infection symptoms including diarrhoea, vomiting and dehydration in pigs, especially in sucking and nursing piglets (Janetanakit et al., ; Ma et al., ; Marthaler, Raymond et al ; Song et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It was identified later in several states of USA (Li et al., ; Marthaler, Jiang, Collins, & Rossow, ; Wang, Byrum, & Zhang, ) and has now spread to South Korea, mainland China, Thailand and Laos (Lee & Lee, ; Lee et al., ; Lorsirigool et al., ; Madapong et al., ; Song et al., ). The emergence of PDCoV was most often associated with clinical infection symptoms including diarrhoea, vomiting and dehydration in pigs, especially in sucking and nursing piglets (Janetanakit et al., ; Ma et al., ; Marthaler, Raymond et al ; Song et al., ). These worldwide outbreaks of PDCoV have caused economic losses to the global commercial swine industry (Chen, Gauger et al., ; Chen, Zhu et al., ; Homwong et al., ; Song et al., ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American PDCoVthat was discovered in Ohio and Indiana, rapidly spread to other states in the USA and Canada, and caused significant economic losses in the swine industry . PDCoV has also been identified in Canada, Thailand, Korea and China (Dong et al, 2015;Homwong et al, 2016;Janetanakit et al, 2016;Lee et al, 2016;Song et al, 2015).Genome analysis has revealed that USAPDCoV isolates share a close relationship (99.7% sequence identity) with Hong Kong and South Korean PDCoV strains, and with CoVsisolated in Asian leopard cat and Journal "Veterinaria i kormlenie" èçìåíåíèé, êîòîðûå èãðàþò êëþ÷åâóþ ðîëü â óìåíüøåíèè âèðóëåíòíîñòè, ýòî ìîaeåò ïîñïîñîáñòâîâàòü ðàçðàáîòêå ýôôåêòèâíûõ âàêöèí.…”
Section: Porcine Delta Coronavirus (Pdcov)mentioning
confidence: 99%
“…The clinical symptoms of PDCoV disease are very similar to those of porcine epidemic diarrhea, but PDCoV disease is milder [4]. Since April 2017, disease caused by PDCoV strains has been reported in North America (the United States, Canada, and Mexico) [5][6][7][8][9][10] and Asia, including South Korea, Mainland China, Thailand, Laos, and Vietnam [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%